Draft IXth Five Year Plan 1997-2002 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1997)
Lakshadweep, one of the world's most spectular tropical island systems is unique in many ways. If you cannot have another Himalayas in India, then you cannot also have another Lakshadweep. Because there are no other coral atolls in the country. Thirty-two sq.Kro of land spread over 36 islands, is surrounded by 4,200 sq.km of lagoons. Untold, rich marine wealth abounds in these lagoons. It is a treasure supported by an extremely fragile ecosystem. The islands are diamonds crowning the lagoons. Made up of coral soil, the land mass is extremely porous so much so that even if it pours, the water is quickly absorbed and none is visible after a few minutes. All of it goes to form a water lense that keeps saline water from coming in and keeps the islands from collapsing.
Union Territory of Lakshadweep